2010
DOI: 10.1371/journal.pone.0012612
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Integration of Glutamatergic Signals by Little SAAS in Novel Suprachiasmatic Circuits

Abstract: BackgroundNeuropeptides are critical integrative elements within the central circadian clock in the suprachiasmatic nucleus (SCN), where they mediate both cell-to-cell synchronization and phase adjustments that cause light entrainment. Forward peptidomics identified little SAAS, derived from the proSAAS prohormone, among novel SCN peptides, but its role in the SCN is poorly understood.Methodology/Principal FindingsLittle SAAS localization and co-expression with established SCN neuropeptides were evaluated by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 64 publications
3
52
0
Order By: Relevance
“…Similarly, intracellular signaling genes including Mapk3, Camk2b , and Prkaca (Zhu et al, 2012) and the neuropeptide signaling gene Pcsk1n , which codes for the precursor molecule of the peptide little-SAAS, were upregulated as well. Since little-SAAS has been reported to be involved in intercellular coordination within the SCN (Atkins et al, 2010), this upregulated behavior suggests that Group 4 plays a synchronizing role in the SCN. Similar to Group 3, these neurons did not show any clear spatial organization (Figure 6B).…”
Section: Resultsmentioning
confidence: 86%
“…Similarly, intracellular signaling genes including Mapk3, Camk2b , and Prkaca (Zhu et al, 2012) and the neuropeptide signaling gene Pcsk1n , which codes for the precursor molecule of the peptide little-SAAS, were upregulated as well. Since little-SAAS has been reported to be involved in intercellular coordination within the SCN (Atkins et al, 2010), this upregulated behavior suggests that Group 4 plays a synchronizing role in the SCN. Similar to Group 3, these neurons did not show any clear spatial organization (Figure 6B).…”
Section: Resultsmentioning
confidence: 86%
“…These subgroups have distinct developmental patterns (Antle, et al 2005b) and are thought to represent distinct subclasses with minimal overlap in neuropeptide expression. However, as the index of SCN peptides grows, it is becoming apparent that SCN neurons can co-express different peptides that may contribute to their functional activity (e.g., Atkins, et al 2010; Drouyer, et al 2010; Geoghegan and Carter 2008; Hundahl, et al 2012; Lee, et al 2015). Although the shell-core scheme of the SCN network continues to be a convenient construct, it will likely morph to become more sophisticated as understanding of SCN circuitry increases (Morin 2007, 2012).…”
Section: Scn Network Organization: Functional Differences Among Neuromentioning
confidence: 99%
“…A recent study demonstrated that SCN network function is regulated by Neuromedin S, which is an SCN peptide produced by both AVP and VIP neurons (Lee et al 2015). Also, a forward peptidomics screen identified little SAS as a novel peptide produced in the SCN core that relays photic signals independent of VIP- or GRP-dependent signaling (Atkins et al 2010). Another interesting development is that intra-SCN glutamatergic signaling may play a role in coupling the left and right SCN (Michel, et al 2013), and yet glutamate has not been detected in the SCN (Strecker et al 1997).…”
Section: Scn Coupling Mechanismsmentioning
confidence: 99%
“…Exposure of mice to low-intensity constant light lengthens the circadian period in rodents while exposure to brighter light leads to arrhythmicity. Alterations in retinohypothalamic signaling, perhaps through altered release of glutamate, pituitary adenylyl cyclase-activating peptide, or little SAAS, could contribute to disrupted SCN function (2,12). To test the functional integrity of the retinohypothalamic tract and SCN responsiveness to lighting information, groups of animals of each genotype were exposed to light for 1 h beginning at CT17, and brains were collected at CT18.…”
Section: Preserved Retinohypothalamic Signaling In Dko Micementioning
confidence: 99%